Pimecrolimus Efficacy and Safety in Management of Children with Atopic Dermatitis - Nikolay N. Murashkin; Ekaterina S. Pavlova; Roman V. Epishev; Alexander I. Materikin; Roman A. Ivanov; Leonid A. Opryatin; Dmitriy V. Fedorov; Mariya A. Leonova; Alena A. Savelova (Вопросы современной педиатрии, 2024)
Atopic dermatitis (AD) is one of the most common inflammatory skin diseases. Early management of AD is crucial for preventing the development of atopic disease such as asthma, allergic rhinitis, etc. Topical glucocorticoids (TGCs) are used as first-line therapy, however, their long-term use poses the risk for patient's health. Despite the rapid clinical response at skin process aggravation, long-term use of TGCs in first-line therapy is associated with various adverse events, including: skin atrophy, hypothalamic-pituitaryadrenal axis suppression, telangiectasis, etc. All together it limits the long-term TGCs use, especially in management of pediatric patients and using such drugs in sensitive regions such as face and intertriginous areas. Due to these limitations TGCs should only be used for a short period of time. Thus, limitations in both treatment duration and number of drugs make TGCs non-optimal for long-term AD treatment. Pimecrolimus (1% cream) is a topical calcineurin inhibitor that is indicated for the treatment of mild to moderate AD. Pimecrolimus does not cause any significant side effects compared to TGCs and it is well tolerated for long-term administration.